KYAI SOLEH DARAT, TAFSIR FA'ID AL-RAHMAN DAN RA. KARTINI - Masrur, Mohammad (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2012)
One of the intellectual heritages of Islam in Java pre modernism. That deserve gets appreciation is the work of shaykh Muhammad ibn Salih al-Samarani Umar , who among Kyai (clerics) in Java is know as ?Saleh Kyai Darat?. Tafsir Faid al- Rahman fi Tarjamah Kalam Malik Dayyan is a monumental work has ever written by him, this Tafseer (interpretation) is not complete 30 Juz, it?s just till the Tafseer (interpretation) of the letter al-nisa, consists of two large volumes of 705 pages thick, Both were printed by the publicher of al-Muhammadiyah, Singapore between the years 1309-1312 H.There are two important notes that need further explored related to the interpretation of the Faid al-Rahman. First, this Tafseer book was specifically written by Kyai Soleh Darat met/fulfill the demands of RA. Kartini, Second, this book had given by Kyai Saleh Darat to RA. Kartini as a gift/gists upon her marriage with RM. Joyodiningrat, who is a Regent of Rembang at the time.